Factors Influencing Customer Satisfaction And Customer Loyalty Toward Social Commerce In Jabodetabek ( Focus On Tiktok Shop ) - Ali Afief Kurniadi; Usep Suhud; Mohamad Rizan (Brilliant International Journal Of Management And Tourism, 2023)
In this context, it is important for companies operating in the field of social e-commerce to understand the factors affecting customer satisfaction and e-loyalty, among others sales promotion, perceived security, e-service quality and trust. Through this research, is expected to provide valuable insights for social e - commerce companies in developing effective customer marketing and management strategies to increase customer satisfaction and e - loyalty, especially in this study directed at the phenomenon of TikTok Shop which is a trend among the public especially during the COVID-19 pandemic a few years back. The results are expected to provide valuable input for TikTok and other social-commerce platforms in improving customer satisfaction and customer loyalty. Keywords: sales promotion, perceived security, e-service quality, trust, customer satisfaction.